The relationship between the stone's composition and the biochemical parameters of blood and urine in patients with urolithiasis - Radouane El Habbani; Rabie Kachkoul; Abdellah Chaqroune; Anissa Lahrichi; Mohamed Mohim; Fatima ezzahra El Oumari; Tarik Sqalli Houssaini (Scientific African, 2023)
Urolithiasis is the most painful and frequent urological disease of the urinary tract. This study is the first in Morocco that aimed to determine the relationship between the urinary stone's composition and the biochemical analysis of blood and daily urine.A total of 154 urinary stones from lithiasis patients was collected between December 2009 and July 2015 at the Hassan II University Hospital in Fez-Morocco. The stones were analysed morphologically and chemically, blood and urine biochemical parameters were established and the relationship between these latter and the stones composition was determined.The stones analysis shows that more than 63% of stones are calcium oxalate, infection stones were more common in patients under 16 years of age. Twenty-two percent of patients had a higher creatinine level and 13% of them had hypercalciuria. However, uric acid stone (UA) patient's group were older than those of whewellite (Wh) group (p = 0.004). The blood creatinine level was significantly high in the UA and weddellite (Wd) groups (p = 0.032), and a significant difference between the two groups, Wh and Wd, for the Calciuria/Creatininuria ratio (p = 0.032). The Principal Component Analysis (PCA) showed a correlation between 24-hour uricuria, 24-hour urine, 24-hour diuresis, 24-hour creatinine, and natriuresis on the one hand, and with calciuria, 24-hour calciuria and BMI on the other hand.These results show the probable effect of different biochemical parameters of urine and blood in certain stones types formation, and presents a contribution to understand the urolithiasis risk factors in order to limit the recurrence of kidney stones and long-term complications